Targeting Health Programs to Reach the Poor - Gwatkin, Davidson R (World Bank, Washington, DC, 2018)
In principle, the efficiency of poverty-oriented social programs can be increased dramatically through “targeting” an infelicitous term applied to efforts to focus development programs more directly on the poor. By one widely-cited estimate, a set of “perfectly targeted” programs -- that is, programs whose benefits reach all the poor and only the poor -- could eliminate poverty at less than 10% the cost of development programs that do not discriminate between poor and rich. No knowledgeable advocate of targeting, no matter how enthusiastic, would claim that the maximum attainable gain from targeting comes anywhere close to the theoretical maximum referred to above. But a measure does not have to be ideal in order to be worthwhile, and this raises the possibility that targeting might still have much to offer. The purpose of what follows is to explore this possibility.